Infographic. the race to reduce injury and illness in professional road cycling - Fallon, T.; Nolan, R.; Rankin, A.; Peters, J.; Heron, N. (British Journal of Sports Medicine, 2025)
Professional cycling is a physically and mentally demanding sport with athletes exposed to high training and racing loads throughout a season. For example, in our cohort of 47 professional cyclists (30 male, 17 female) monitored over 366 days, male athletes accumulated over 6000 hours of racing and 21 000 hours of training, while female athletes logged over 2500 hours of racing and nearly 10 000 hours of training. While injuries and illnesses are common, they are also disruptive, impacting the overall well-being of the athlete, training and competition availability, and in some cases, competitive career longevity. Cycling`s world governing body, the Union Cycliste Internationale, recently highlighted the importance of injury and illness epidemiology in their 2030 agenda in a drive to `promote and support research in cycling epidemiology and medicine`. This was the first study to present the prevalence, patterns and implications of injuries and illnesses in a team of professional male and female cyclists over an entire competitive season covering over 1 million km.